Concentration levels of selected hormones in judokas and the extent of their changes during a special performance test at different ambient temperatures - Palka, T.; Rydzik, L.; Tota, L.; Koteja, P.; Ambrozy, T.; Mucha, D.; Szpotowicz-Czech, B.; Lech, G.; Javdaneh, N.; Czarny, W. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background There is little scientific literature available on the diversity of physiological responses of judokas to anaerobic interval exercises in warm environments. Understanding the dynamics of changes in the concentration of selected hormones during a special endurance test at different ambient temperatures may have significant practical value, as it provides an opportunity for optimal programming and monitoring of the training process. So, the main aim of the research was to survey interval anaerobic exercises in different ambient temperatures on Concentration levels of selected hormones in judokas.